Visible-light-induced cascade radical ring-closure and pyridylation for the synthesis of tetrahydrofurans. Issue 8 (25th March 2019) - Kim, Yechan; Lee, Kangjae; Mathi, Gangadhar Rao; Kim, Inwon; Hong, Sungwoo
Abstract : A novel visible-light-enabled alkoxy radical ring-closure and pyridylation from N -alkenyloxypyridinium salts was achieved under metal-free mild conditions, offering a powerful synthetic tool for assembling various pyridine-tethered tetrahydrofurans. Abstract : Reported is a novel visible-light-enabled alkoxy radical ring-closure and pyridylation from N -alkenyloxypyridinium salts serving as both alkoxy radical precursors and heteroaryl sources. This strategy features a photoredox tandem radical process involving a sequential fragmentation of an N -alkoxypyridinium salt, a radical cyclization process, and a pyridylation process. This method exhibited broad substrate scope, good functional group compatibility, and metal-free mild conditions, offering a powerful synthetic tool for assembling various pyridine-tethered tetrahydrofurans and late-stage functionalization of complex biorelevant molecules. Moreover, radical cascade cyclization could be successfully achieved, leading to the synthesis of previously challenging and important pyridine-tethered bicyclic oxaspiro ring systems.